‘Story Bird’ As A Platform For Writing Classroom - Aminah, Aminah; Syahputra, M. (CV. ITTC INDONESIA, 2023)
Writing is a process of transferring your ideas in written form. It is not an easy thing to do because there are some rules that we should follow in order to make our messages deliver to the reader. The aim of this study is to investigate the use of Story Bird application in teaching writing. This research belongs to descriptive library research by analysis the content of documents. It can be seen that storybird as a web 2.0 tool is really appropriate to use in writing classroom. It offers some advantages including the allowing collaborative work, easy to organize work, allowing students to publish their work that can increase their motivation to write. This research is recommended to use in teaching writing.